Dasatinib and Quercetin alleviate type 2 diabetic osteoporosis by regulating serum metabolite and gut microbiome - Yang, Junzheng; Zhang, Hua; Gu, Zhuoxu; Zhou, Guanghui; Liang, Guihong; Zeng, Lingfeng; Zhao, Jinlong; Yang, Weiyi; Liu, Jun; Pan, Jianke (Frontiers in Microbiology, 2025)
Type 2 diabetic osteoporosis (T2DOP) is a complex metabolic bone disorder characterized by reduced bone density and increased risk of osteoporosis in patients with type 2 diabetes mellitus. The etiology of T2DOP is multifactorial, involving hyperglycemia, insulin resistance, and gut microbiota dysbiosis. Current management strategies for T2DOP typically involve a comprehensive approach, including strict glycemic control, vitamin D and calcium supplementation, anti-osteoporotic medications, increased physical activity, and gut microbiota modulation. This study aimed to investigate the therapeutic potential of the combination of Dasatinib and Quercetin (D + Q), known as senolytics, in treating T2DOP. To elucidate the underlying mechanisms, a well-characterized T2DOP mouse model was established. Bone mass was evaluated using micro-computed tomography and histological staining techniques. Subsequently, the impact of D + Q treatment on gut microbiota composition and complex serum metabolite profiles was comprehensively examined. The results demonstrated that D + Q reshaped gut microbiota, resulting in increased short-chain fatty acid producers (Lachnospiraceae and Bacteroides) and decreased proinflammatory bacteria (Mucispirillum), which were associated with the therapeutic effects in bone-fat balance. Additionally, D + Q treatment enhanced amino acid and short-chain fatty acid metabolism while simultaneously reducing cholesterol and triglyceride levels.